Isolation of the major phenolic compounds in the pits of brined green olive drupes: structure elucidation by comprehensive 1H/13C-NMR spectroscopy - Khallouki, Farid; Hull, William Edmund; Würtele, Gerd; Haubner, Roswitha; Erben, Gerhard; Owen, Robert (Natural product communications, 2019)
Pits of representative green olive drupes from Italy and Greece were evaluated for their content of phenolic compounds. The major purified polyphenols quantitated in mg/kg in the Italian and Greek pit varieties, respectively, were tyrosol (157 and 523), hydroxytyrosol (3 386 and 1723), vanillin (151 and 83), vanillic acid (58 and 101), phloretic acid (85 and 0), (+)-pinoresinol (954 and 877), (+)-1-acetoxypinoresinol (114 and 105), dehydrodiconiferyl alcohol (340 and 386) and the corresponding aldehyde (398 and 553), the erythro and threo isomers of guaiacylglycerol-β-coniferol ether (78 and 147) and (93 and 273) and their corresponding aldehydes (238 and 349) and (232 and 537), and finally nüzhenide (186 and 364). The data indicate that the waste products of olive mills should be a rich source of a variety of polyphenolic compounds. Detailed 1H- and 13C-nuclear magnetic resonance data are presented, representing the most comprehensive and unambiguous results available to date for the compounds studied.
im Titelzusatz sind die Zahlen '1' und '13' hochgestellt
Gesehen am 05.12.2019